Pengembangan Perangkat Lunak Pendampingan Mahasiswa Disabilitas (Studi Kasus : Pusat Studi Layanan Disabilitas Universitas Brawijaya) - Harun Arrasyid Hasibuan; Fajar Pradana; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The Center for Disability Study and Services Universitas Brawijaya (PSLD) conducts the mentoring process for students with disabilities every day. The scheduling process for mentoring students with disabilities is done by matching the disability student and volunteer schedules and verifying mentoring manually by looking at the mentoring logbook that has been filled out by volunteer students every week, which makes scheduling and verification of mentoring results ineffective because of the long and unknowable process the results directly. PSLD also does not yet have a reporting media that can be used to channel aspirations and complaints experienced by students so that students cannot report directly and cannot know the progress of the proposed report. Disability student assistance software is a system that has the goal of solving problems experienced by PSLD. The system can schedule the mentoring automatically based on the empty schedule of students, recap the mentoring process, and can provide functions for reporting. The system is developed through the stages of determining user needs, carrying out design, implementation, and testing. Testing is done using unit testing, validation, and compatibility with 100% valid results, and all functions can run well in several test environments.